Artificial intelligence in 2.0 International arbitration. Opportunities and challenges in a future that is already present - Gonzalo Quiroga, Marta (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Artificial intelligence (AI) is the hot topic. Its vertiginous and disruptive irruption raises in arbitration a series of legal and practical questions methodologically addressed in this investigation. AI, and the technologies derived from it, allow the creation of tools that introduce unprecedented challenges, as well as unusual opportunities, in all phases of arbitration. Specialized programs that assist from the appointment of arbitrators to the drafting and execution of awards, generate some concern about their veracity, regulation, control, data, confidentiality, transparency, the possibility of robot arbitrators?... All this is scientifically examined here with the guarantees, precautions and responsibility required by the analysis of AI in International Arbitration 2.0, a future that is already here.
Keywords: Artificial Intelligence (AI); 2.0 International Arbitration; Regulation; Confidentiality; ODR